Rancang Bangun Aplikasi Perjalanan Dinas berbasis Laravel dan Vue (Studi Kasus : Balai Guru Penggerak Kalbar) - Aditya Pratama; Denny Primanda; Nurman Hariyanto; Adha Maulana (Journal of Information Technology, 2023)
Business travel applications have become an important element in managing administration and staff mobility in various organizations and institutions. However, previously BGP KALBAR did not have an official travel application that suited their needs. This results in a number of problems, such as less efficient manual management, lack of transparency in official travel management, and an unsatisfactory experience for BGP KALBAR staff and teachers. This research aims to design and develop an official travel application based on Laravel and Vue.js for the West Kalimantan Teacher Mobilization Center (BGP KALBAR). This application aims to increase efficiency and transparency in official travel management, as well as provide a better experience for BGP KALBAR staff and teachers. The development methodology uses a combination of Laravel as the back-end framework and Vue.js as the front-end framework. Laravel provides powerful capabilities in database management and business logic, while Vue.js enables the creation of interactive and responsive user interfaces. The application includes features such as travel management, reporting and integration with MySQL database. The results of the testing show that the system proposed in this research functions well. Based on the measurement results from the MOS (Margin of Satisfaction), the application that has been developed is able to overcome problems related to the Official Travel Application at the West Kalimantan Teacher Mobilization Center.